2015
DOI: 10.17221/1005/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of nitrogen and sulphur fertilization on yields and value of N:S ratio for Lolium × boucheanum

Abstract: This paper deals with the efficiency of nitrogen (N) and sulphur (S) fertilization on yields and value of N:S ratio for hybrid ryegrass cultivated in monoculture and in a mix with white clover. The research was carried out from 2011-2013 near Krakow in southern Poland. Plants were evaluated in the context of diversified fertilization with nitrogen at rates of 50 and 100 kg N/ha as well as two sulphur-based fertilizers: Arista siarka and Pro-siarka, used at rates of 5, 10, 15 kg S/ha. Independent research findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Grygierzec et al. (2015) reported yield increases of 520–2080 kg ha –1 with the addition of 15 kg S ha –1 to a 50 kg N ha –1 treatment in grassland trials conducted on a silt loam in Poland between 2011 and 2013, responses more similar to those seen in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Grygierzec et al. (2015) reported yield increases of 520–2080 kg ha –1 with the addition of 15 kg S ha –1 to a 50 kg N ha –1 treatment in grassland trials conducted on a silt loam in Poland between 2011 and 2013, responses more similar to those seen in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Our results are consistent with other studies that report a significant yield response of different crops to sulfur fertilization [25,27,34,36]. However, there are also reports indicating that plant growth response to sulfur addition is not always so positive and unequivocal [17,37]. Under field conditions, the response of plants to sulfur application is complex (among other immobilization, mineralization, leaching processes may have great impact) and, despite numerous studies, the exact requirements for sulfur fertilization are not known [34].…”
Section: Fresh and Dry Masssupporting
confidence: 90%
“…Nitrogen is one of the most important yield forming factors in agriculture. Literature data indicate that plant nitrogen content is significantly modified by the plant-available sulfur in the soil [27,37]. The results showed that the nitrogen content varied from one swath to the next, with the smallest differences (mostly statistically insignificant) occurring in the first swath (Table 2).…”
Section: Nitrogen Content and Uptakementioning
confidence: 96%
“…Bedoussac and Justes (2011) reported that grasses and legumes are more suitable for the organic system that equals low N fertilisation, in comparison with conventional ones. Moreover, reduced mineral fertilisation with 0 1 2 3 4 5 6 7 8 0 1 2 3 4 5 6 7 8 0 1 2 3 4 5 6 7 0 1 2 3 4 5 6 7 8 0 1 2 3 4 5 6 7 8 0 1 2 3 4 5 6 7 (Grygierzec et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Absorption of nitrogen (N) by plants is closely related to the amount of sulfur (S) they receive; in Poland S shortages in agroecosystems tend to occur particularly in crop production with intensive N fertilisation. Therefore, there is a concern that the traditionally used NPK fertilisation is not balanced and the S deficit may limit the utilisation of other nutrients by plants (Grygierzec et al 2015). One of the key fodders among the legumes grown in moderate climate…”
mentioning
confidence: 99%